Элитное воинское погребение предскифского времени из окрестностей г. Майкопа - Эрлих, В.Р. (Археологія і давня історія України, 2019)
В статье рассматривается комплекс богатого протомеотского погребения 3 могильника
«Улька I», открытого в 2017 г. в окрестностях
г. Майкопа. Основываясь на том, что в погребении содержится имитация повозки или колесницы,
присутствует полный набор вооружения, импортные предметы, изделия из драгоценных металлов,
автор полагает, что данное погребение принадлежит представителю высшей воинской элиты протомеотского общества, возможного участника
походов в Закавказье и датирует его второй половиной VIII в. до н. э. The Ulka I cemetery was discovered on the site of
the ancient Ulka settlement during rescue excavations conducted by A. V. Surkov in 2017. It is located 5.4 km
northeast of Maykop (Adygea, RF). A total of four Proto-Maeotian burials were uncovered in these burial
grounds. This article focuses on the wealthiest burial 3, which contained the remains of a warrior flanked by two
horse skulls to the south — apparently in imitation of a cart or chariot. The burial inventory consisted of a long
bimetallic sword with a length of 108 cm, a spearhead, a quiver with nine bronze arrows, gold and silver pendants
of the «Šarengrad» type, gold-plated bronze buttons and various other items. Ananalysis of the funeral inventory
shows that the main items belong to the Chernogorovka or Pre-Novocherkassk category of Proto-Maeotian material.
However, the burial also contains later chronological indicators, e. g. arrowheads of the «Novocherkassk
type» and aclasp of the «Slobodzeya» type. In general, it is possible to suggest a dating within the second half of
the 8th century BC for the complex. The burial inventory indicates that the deceased belonged to the highest
military elite of Proto-Maeotian society. He probably took part in military campaigns in the Trans-Caucasus,
owned multiple herds of horses, and oversawtransactions and exchange with the elite of Central Europe.